2020
DOI: 10.1101/2020.02.03.931733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perinatal THC Exposure via Lactation Induces Lasting Alterations to Social Behavior and Prefrontal Cortex Function in Rats at Adulthood

Abstract: 175 words Main text: 3871 words Figures: 4 main, 5 tables AbstractCannabis is the world's most widely abused illicit drug and consumption amongst women during and surrounding the period of pregnancy is increasing. Previously, we have shown that cannabinoid exposure via lactation during the early postnatal period disrupts early developmental trajectories of prefrontal cortex maturation and induces behavioral abnormalities during the first weeks of life in male and female rat progeny. Here, we investigated the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 50 publications
(72 reference statements)
2
14
1
Order By: Relevance
“…Our work revealed that exposure of lactating females to either THC, or a synthetic agonist of CB1R, altered the maturational trajectory of GABAergic transmission and led to behavioral abnormalities in early life (Scheyer et al, 2020b). Very recently, we reported that perinatal THC exposure via lactation elicited lasting, deleterious impacts on social behavior and synaptic plasticity in the PFC of the adult offspring (Scheyer et al, 2020a).…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Our work revealed that exposure of lactating females to either THC, or a synthetic agonist of CB1R, altered the maturational trajectory of GABAergic transmission and led to behavioral abnormalities in early life (Scheyer et al, 2020b). Very recently, we reported that perinatal THC exposure via lactation elicited lasting, deleterious impacts on social behavior and synaptic plasticity in the PFC of the adult offspring (Scheyer et al, 2020a).…”
Section: Introductionmentioning
confidence: 75%
“…The magnitude of plasticity was calculated at 0-10min and 30-40 min after induction (for TBS-LTP and eCB-LTD) or drug application (mGlu2/3-LTD) as percentage of baseline responses (Scheyer et al, 2020a). Statistical analysis of data was performed with Prism (GraphPad Software) using tests indicated in the main text after outlier subtraction (Grubb's test, alpha level 0.05).…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 3 more Smart Citations